2017
DOI: 10.3325/cmj.2017.58.281
|View full text |Cite
|
Sign up to set email alerts
|

IgM as a novel predictor of disease progression in secondary focal segmental glomerulosclerosis

Abstract: AimTo determine the role of immunoglobulin M (IgM) deposits in clinical manifestations, disease outcome, and treatment response of idiopathic and secondary focal segmental glomerulosclerosis (FSGS).MethodsKidney biopsy specimens of 171 patients diagnosed with FSGS (primary and secondary) and 50 control patients were retrospectively included in the study. For each patient, clinical and outcome data were obtained and compared to morphological parameters, including immunofluorescence analysis of mesangial IgM and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Until recently, significance of these pathological findings has been unclear, yet Strassheim et al [12] demonstrated that IgM deposits activated the classical and alternative pathways (APs) of the complement system within the glomerulus and contributed to disease progression in adriamycin nephropathy, an animal model of FSGS. The importance of these depositions on the disease course of patients with primary FSGS is still obscure [8, 13]; we therefore aimed to investigate the significance of glomerular IgM and C3 deposition on clinical and pathological features and outcomes of adult patients with primary FSGS.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, significance of these pathological findings has been unclear, yet Strassheim et al [12] demonstrated that IgM deposits activated the classical and alternative pathways (APs) of the complement system within the glomerulus and contributed to disease progression in adriamycin nephropathy, an animal model of FSGS. The importance of these depositions on the disease course of patients with primary FSGS is still obscure [8, 13]; we therefore aimed to investigate the significance of glomerular IgM and C3 deposition on clinical and pathological features and outcomes of adult patients with primary FSGS.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the above relevance of glomerular IgM deposition in patients with lupus nephritis, it is important to evaluate the predictive value of glomerular IgM deposition for long-term renal outcome in lupus nephritis. Recently, several studies showed that IgM deposition predicted renal outcome in patients with IgAN, FSGS and diabetic nephropathy [7,9,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In another animal model of adriamycin-induced focal segmental glomerulosclerosis (FSGS), IgM deposition activated the complement system and mediated glomerular injury [6]. In the subsequent clinical studies, IgM deposition independently associated with worse renal outcomes in patients with various glomerular diseases, including FSGS, IgA nephropathy (IgAN), and diabetic nephropathy (DN) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our study, it has been shown that patients who have IgAN with IgM deposition have a higher C1q deposition rate and more severe Oxford classi cation (statistically signi cant differences in mesangial proliferation, endocapillary proliferation, segmental sclerosis, and crescents) [22]. There should be no signi cant difference in immune complex deposition in the glomeruli in patients with typical FSGS lesions, thin basement membrane nephropathy, and mild glomerular lesions, but one study showed that patients with FSGS lesions had a signi cantly higher IgM deposition rate than patients with thin basement membrane nephropathy and mild glomerular lesions (55.4% vs. 30.0%) [23]. In addition, other studies have shown that patients with IgM nephropathy who present with only IgM deposits in the mesangial area are more likely to progress to FSGS lesions as con rmed by repeat renal biopsy [24][25][26].…”
Section: Discussionmentioning
confidence: 99%